Relationship between plasma uric acid levels, antioxidant capacity, and oxidative damage markers in overweight and obese adults: A cross-sectional study. - Natalia Albuja-Quintana; Aida M Chisaguano-Tonato; Maria E Herrera-Fontana; Sandra Figueroa-Samaniego; José M Alvarez-Suarez (PLoS ONE)
Obesity, a complex metabolic chronic illness, is commonly accompanied by an excessive production of free radicals, which influences the development of its comorbidities. Uric acid is commonly linked to pro-oxidant effects on human health. Though recent evidence suggests its potential antioxidant properties, it is possible that the increase in circulating uric acid levels is an adaptive protective response against the detrimental effects of excess free radicals and oxidative stress present in obese individuals. Hence, the purpose of this study was to evaluate the association between antioxidant capacity and oxidative damage markers with uric acid levels in overweight and obese individuals who live at sea level. This cross-sectional study included 93 adult volunteers (28 men and 65 women) from the city of Machala, El Oro, Ecuador, divided into three study groups according to Body Mass Index (normal weight, overweight, and obese). Sociodemographic characteristics, lifestyle elements, and physical measurements were evaluated, and blood samples were collected from all participants. Antioxidant and oxidant markers, including Radical-Scavenging Activity Assay (DPPH), Ferric Reducing Ability of Plasma (FRAP), Catalase (CAT) activity, Thiobarbituric Acid Reactive Substances (TBARS), and Protein Thiol Groups (SH groups), were assayed in the plasma samples. Coefficients of correlations and linear regression models were applied to evaluate the association between antioxidant/oxidant parameters and plasma uric acid levels. The antioxidant capacity, as measured by FRAP scavenging and CAT, was significantly higher in the obese group compared to the normal weight group, and uric acid levels presented a significant positive association with FRAP (b: 0.578, R: 0.459, p: 0.003) and CAT activity (b: 1.326; R: 0.432, p: 0.005) in overweight and obese individuals. Consequently, the presented evidence supports the potential antioxidant role of uric acid in the pathogenesis of obesity, contributing to our understanding of oxidative stress and inflammation that characterizes this illness.